Localization-driven metal-insulator transition in epitaxial hole-doped Nd 1−x Sr x NiO 3 ultrathin films - Wang, Le (2016)
Advances in thin film growth technologies make it possible to obtain ultra-thin perovskite oxide films and open the window for controlling novel electronic phases for use in functional nanoscale electronics, such as switches and sensors. Here, we study the thickness-dependent transport characteristics of high-quality ultrathin Nd0.9Sr0.1NiO3 (Sr-NNO) films, which were grown on LaAlO3 (0 0 1) single-crystal substrates by using pulsed laser deposition method. Thick Sr-NNO films (25 unit cells) exhibit metallic behavior with the electrical resistivity following the T  n (n  <  2) law corresponding to a non-Fermi liquid system, while a temperature driven metal–insulator transition (MIT) is observed with films of less than 15 unit cells. The transition temperature increases with reducing film thickness, until the insulating characteristic is observed even at room temperature. The emergence of the insulator ground state can be attributed to weak localization driven MIT expected by considering Mott–Ioffe–Regel limit. Furthermore, the magneto-transport study of Sr-NNO ultrathin films also confirms that the observed MIT is due to the disorder-induced localization rather than the electron–electron interactions.